Intramolluscan stages of digeneans parasitizing the pest apple snail Pomacea canaliculata from Argentina: Molecular identification and histopathology - Martinez, Lorena Evangelina (2025)
Pomacea canaliculata is a highly successful invasive snail that shapes freshwater communities in both native and invaded habitats. We studied its digenean parasites from three freshwater bodies in its native distribution area in Buenos Aires Province, Argentina. An integrated approach was used to determine and describe the larval stages of digenean, including morphological, molecular, and histopathology analyses. We provide the first record of P. canaliculata as the first intermediate host of Stomylotrema vicarium (Stomylotrematidae), two species of the family Phaneropsolidae, and one species of the family Cyclocoelidae. This is also the first record of a species of the family Cyclocoelidae parasitizing snails of the genus Pomacea, with the apple snail acting as both the first and second intermediate host. The digestive gland was identified as the target organ of infection for all species. Stomylotrema vicarium and Phaneropsolidae gen. et sp. 2 alter the structure of the gonads, causing indirect parasitic castration, and, through mechanical compression, destroying also the digestive gland. Adequate knowledge of the identity and dynamics of the parasites affecting P. canaliculata in its native range and the damage they cause is key to explaining the success of this invasive species. The lack of parasite records in invaded areas supports the “enemy release” hypothesis, which could explain the apple snail’s success in these environments. Parasitic castration reduces the reproductive potential of hosts, limiting the expansion and competition of invasive species, making it crucial to understand these impacts for their conservation and control.